Marco constitucional del uso del velo y del pañuelo islámico en la sociedad española contemporánea: ¿Señas de identidad ideolígica y/o ultural? - Pérez Álvarez, Salvador (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2012)
The term hijab has commonly been used to talk about the veiling of Muslim women as a duty imposed by their religious beliefs. Beyond this fact, it is the manifestation of the Dress Code of Conduct that some mandates of the divine revelation contained in the original sources of Islamic Law imposed on Muslim believers. The result of these contradictions is that they focus on the original meaning of the rules of classical Islamic Law, namely, the idea that wearing the full veil and headscarf in the public sphere is a religious duty for Muslim women living in democratic societies. The study of this issue is necessary in order to establish requirements that may condition the right to use this type of dress in the public sphere in accordance with the representative values of the Spanish Constitutional Law.
Keywords: Islamic veil; Islamic headscarf; ideological freedom; right to self-image; public sphere; Spanish Constitutional Law.